The role of climate on Covid-19 spread in France. - Aboura, Sofiane (International Journal of Environmental Health Research, 2023)
This paper investigates the influence of climate on the transmission of the SARS-CoV-2 virus in France. Ordinary, time-varying, and threshold regressions of the number of cases and deaths are run on weather and government variables. The main findings support the role of climate in Covid-19 spread. The results reveal that a rise in temperatures is negatively associated with reported deaths, while an increase in relative humidity or wind and a decrease in precipitations are negatively associated with confirmed cases. These weather variables appear statistically significant only during the winter season.